2016
DOI: 10.1371/journal.pone.0154475
|View full text |Cite
|
Sign up to set email alerts
|

Seeing Circles and Drawing Ellipses: When Sound Biases Reproduction of Visual Motion

Abstract: The perception and production of biological movements is characterized by the 1/3 power law, a relation linking the curvature and the velocity of an intended action. In particular, motions are perceived and reproduced distorted when their kinematics deviate from this biological law. Whereas most studies dealing with this perceptual-motor relation focused on visual or kinaesthetic modalities in a unimodal context, in this paper we show that auditory dynamics strikingly biases visuomotor processes. Biologically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…The strong link between the modulation of the endpoint speed and the perceived shape was also demonstrated by experimental alterations of speed feedback (presented either by sounds (Thoret et al 2016) or visual point light displays (Viviani and Stucchi 1989;Viviani and Stucchi 1992) which biased visual perception of elliptical shapes. Conversely, the present study confirmed that the instruction to maintain a constant movement-sound relationship induces the stability of the drawing movement shape.…”
Section: Discussion Of Experimentsmentioning
confidence: 87%
See 1 more Smart Citation
“…The strong link between the modulation of the endpoint speed and the perceived shape was also demonstrated by experimental alterations of speed feedback (presented either by sounds (Thoret et al 2016) or visual point light displays (Viviani and Stucchi 1989;Viviani and Stucchi 1992) which biased visual perception of elliptical shapes. Conversely, the present study confirmed that the instruction to maintain a constant movement-sound relationship induces the stability of the drawing movement shape.…”
Section: Discussion Of Experimentsmentioning
confidence: 87%
“…To that purpose, we chose an ecologically valid mapping based on the metaphor of friction sounds (e.g. chalk on a blackboard) inspired by the work of Kronland-Martinet's team who demonstrated that replaying friction sounds (recorded or synthesized) can evoke the shape of the ellipse drawings (Thoret et al 2014) and induce a sensorimotor perceptive bias on the reproduction of visual motion (Thoret et al 2016). In the present study, the participants had to draw repetitively ellipses while maintaining a constant sonification pattern (i.e.…”
Section: General Introductionmentioning
confidence: 99%
“…Sonification has already been shown to influence user movement execution. For instance, Thoret et al [14] asked participants to draw a circle without being able to see their hands while a sound evoking an elliptical movement was played. The participants drew elliptical shapes, demonstrating that sound used in real-time could affect the movement.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, when auditory feedback is provided as an error signal, it reduces endpoint error in healthy subjects by 17%–31% (Hocherman et al, 1988 ; Hocherman, 1993 ), improving the sense of body position. Moreover, it has been shown that real-time auditory feedback in the form of timbre variations (Thoret et al, 2016 ) or sonification (Danna et al, 2015 ) can substantially alter motor performance.…”
Section: Introductionmentioning
confidence: 99%